Природа розсiяння свiтла водними розчинами спиртiв в околi їх особливих точок - Gotsulskiy, V. Ya.; Chechko, V. E.; Melnik, Yu. A. (Publishing house "Academperiodika", 2019)
The physical nature of the anomalous peak observed in a vicinity of the singular point in molecular light scattering spectra of diluted aqueous alcohol solutions is analyzed. The singular point corresponds to an unstable state of the solution, in which water molecules are distributed in monolayers around the alcohol molecules. In a vicinity of the singular point, the solution is shown to become inhomogeneous on nano- and mesoscales. Spatial inhomogeneities are formed by two phases, which are similar by their properties, and the phases transitions between them have a fluctuation character. The process of slow establishment of the equilibrium state in aqueous alcohol solutions (for days and longer) is explained by the similarity of thermodynamic properties of those phases. Using the dynamic light scattering, it is shown that if the solution in the equilibrium state is mechanically excited, the character of relaxation has a periodic component, which corresponds to the transitions between the indicated phases. The summation of two peaks associated with independent light scattering in two mesophases makes the anomalous peak of light scattering asymmetric.